EXPLORING THE LINK BETWEEN LANGUAGE OF INSTRUCTION AND EDUCATIONAL OUTCOMES IN GHANA - Mahama, E. S.; Bawa, J. A. (UDS International Journal of Development, 2022)
The language of instruction in many African countries has been the language of the colonial masters but, citizens of these respective African countries seem to have different opinions regarding the appropriateness and benefits of these foreign languages. Till date, many of these countries have not had a stable education language policy. This study investigated the educational language policy in Africa, using Ghana as a case study, mainly focusing on existing literature. The key findings have been that language in education policy in Ghana has shifted between the use of English language and a local language in the early years of formal education, from the use of the mother tongue or L1 for the first three years of education as the medium of instruction and English as a subject from the fourth year to tertiary level. The review has also found that Ghanaâ€™s justification of the policy to use the mother tongue or L1 is based mainly on studies around the world rather than empirical studies from Ghana. Â There has also not been commitment on the part of the basic schools to enforce the use of the mother tongue as a medium of instruction for the first three years, as stipulated in the language policy. The study therefore concludes, that to some extent, and especially, in rural communities the intended outcomes such as acquiring knowledge, creating opportunities for a majority of people to acquire skills leading to jobs and consequently the well-being of people has not been achieved. It was also found that there is a mismatch between the preference of the citizenry and the policy planners on the language for early years of formal education. The study suggests that given the new trend of multilingualism, issues of language and power, more empirical studies should be conducted on multilingualism in Ghana and wide consultations be made with the citizenry for an accepted education language policy. Keywords: Education, language, mother tongue, policy, educational outcomes.